2015
DOI: 10.1037/tep0000032
|View full text |Cite
|
Sign up to set email alerts
|

Competency-based postdoctoral research training for clinical psychologists: An example and implications.

Abstract: To address the need to respond to challenges in training researchers in clinical psychology, we describe an example of a competency-based postdoctoral training program that emphasizes leadership in writing scientific publications, preparing research grant proposals, integrating research and practice, and the responsible conduct of research. Key program features that can be applied in a range of settings include a systematic approach to setting goals and monitoring progress in achieving key research-related com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Historically, some disciplines, such as psychology, engineering and the biological sciences, have used PDRF as a form of advanced training to extend their graduates’ research competencies beyond graduate level training [1417]. PDRFs are known to have been part of the European academia for centuries and later exported to the USA in the 1870s [18].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, some disciplines, such as psychology, engineering and the biological sciences, have used PDRF as a form of advanced training to extend their graduates’ research competencies beyond graduate level training [1417]. PDRFs are known to have been part of the European academia for centuries and later exported to the USA in the 1870s [18].…”
Section: Introductionmentioning
confidence: 99%
“…The postdoctoral period should be a functional, fluid, and formative period in a researcher's career (Su, 2013;Drotar et al, 2015). Previous work has demonstrated that outputs during the postdoctoral period can be affected by environmental factors (Felisberti and Sear, 2014), as well as by gender (Borrego et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals may develop priorities for a research career during graduate school and seek a research training position such as a National Research Service Award, for example. The advantages of a mentored research position are clear for a career focused on becoming a funded researcher (National Research Council of the National Academies, 2005), though some research positions may not offer sufficient training for licensure or advanced competency development (Drotar et al, 2015). The choice to forgo HSP postdoctoral training to focus solely on research training may have implications for future investigators, particularly for those who conduct clinical trials or provide supervision for study therapists.…”
Section: Research/teaching and Practice Prioritiesmentioning
confidence: 99%